2015
DOI: 10.1128/jcm.00008-15
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and EasyIn SilicoSerotyping of Escherichia coli Isolates by Use of Whole-Genome Sequencing Data

Abstract: c Accurate and rapid typing of pathogens is essential for effective surveillance and outbreak detection. Conventional serotyping of Escherichia coli is a delicate, laborious, time-consuming, and expensive procedure. With whole-genome sequencing (WGS) becoming cheaper, it has vast potential in routine typing and surveillance. The aim of this study was to establish a valid and publicly available tool for WGS-based in silico serotyping of E. coli applicable for routine typing and surveillance. A FASTA database of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
619
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 730 publications
(623 citation statements)
references
References 35 publications
3
619
1
Order By: Relevance
“…Importantly, since the frequency of nontypeability of in vitro serotyped P. aeruginosa isolates may amount to Ͼ65% (10), analysis with PAst is clearly advantageous and superior compared to conventional in vitro serotyping. Importantly, the superiority of the PAst tool as a reliable and fast typing method is consistent with that of other published tools for in silico serotyping (31)(32)(33)(34)(35). Similar to SerotypeFinder (in silico serotyping of Escherichia coli) (31), LisSero (in silico serotyping of Listeria monocytogenes) (34,35), and SeqSero (in silico serotyping of Salmonella) (32), PAst resolves the OSA cluster information to the most accurate typing possible as a serogroup representing 1 to 3 serotypes.…”
Section: Discussionsupporting
confidence: 51%
“…Importantly, since the frequency of nontypeability of in vitro serotyped P. aeruginosa isolates may amount to Ͼ65% (10), analysis with PAst is clearly advantageous and superior compared to conventional in vitro serotyping. Importantly, the superiority of the PAst tool as a reliable and fast typing method is consistent with that of other published tools for in silico serotyping (31)(32)(33)(34)(35). Similar to SerotypeFinder (in silico serotyping of Escherichia coli) (31), LisSero (in silico serotyping of Listeria monocytogenes) (34,35), and SeqSero (in silico serotyping of Salmonella) (32), PAst resolves the OSA cluster information to the most accurate typing possible as a serogroup representing 1 to 3 serotypes.…”
Section: Discussionsupporting
confidence: 51%
“…Since phenotypic determination of the H antigen can be in vain due to nonmotility, the unavailability of antisera, or unspecific cross-reactions, molecular methods, e.g., fliC RFLP (18) or sequence-based approaches (49), should be applied.…”
Section: Discussionmentioning
confidence: 99%
“…The serotype of each strain analyzed in this study was confirmed using the genes deposited in the Center for Genomic Epidemiology (http://www.genomicepidemiology.org) for E. coli as part of their Web-based serotyping tool (SerotypeFinder 1.1 [https://cge.cbs.dtu .dk/services/SerotypeFinder]) (22,23). We used Ridom to perform batch screening of the genomes analyzed.…”
Section: Methodsmentioning
confidence: 99%